Bowel contrast-enhanced ultrasound perfusion imaging in the evaluation of Crohn's disease patients undergoing anti-TNFα therapy. Issue 6 (June 2021) - Laterza, Lucrezia; Ainora, Maria Elena; Garcovich, Matteo; Galasso, Linda; Poscia, Andrea; Di Stasio, Enrico; Lupascu, Andrea; Riccardi, Laura; Scaldaferri, Franco; Armuzzi, Alessandro; Rapaccini, Gian Ludovico; Gasbarrini, Antonio; et al.
Abstract: Aim: To evaluate whether changes in bowel perfusion parameters measured by dynamic-CEUS (D-CEUS) can be used for monitoring response to therapy in active Crohn disease (CD). Methods: Fifty-four CD patients were evaluated with d -CEUS before (T0) and after 2 (T1), 6 (T2) and 12 weeks (T3) of anti-TNFα therapy. Variations from baseline were calculated for: peak intensity, PI; area under the curve, AUC; slope of wash in, Pw ; time to peak, TP; mean transit time, MTT (median percentage values) and were correlated with combined endoscopic/clinical response after 12 weeks and clinical relapse within 6 months. Results: 70% of patients achieved combined endoscopic/clinical response (responders). The reduction in PI, AUC, Pw and MTT between T1 and T0 was higher in responders. Relapsers (21%) showed significantly lower reduction in delta PI and Pw at T1 and T2. At T3 they showed a new increase in PI and lower reduction in delta Pw. In relapsers, AUC showed a significantly lower decrease at T2 and T3, TP showed a significant reduction at T3 and MTT showed a progressive increase at the different time-points, reaching the statistical significance at T3. Conclusions: d -CEUS might become a reliable predictor of combined endoscopic/clinical response and clinical relapse in CD.